THE ECONOMIC PHENOMENON OBSERVED BY ECONOMICS AND ECONOMIC SOCIOLOGY - Cássio de Oliveira Santos, Gilson (Revista Desenvolvimento Social, 2020)
This work comes to show the economic phenomenon, so, the terms of trade of goods, from the prism of economics as a science and economic sociology, trying to highlight the different perspectives of such analyzes of the economy starting from the classical school Adam Smith, through the marginalist school Javons and Walras Chagar to the institutional and neoinstitucional schools Veblen and Williamson respectively. And finishing with the observations of economic sociology, transitioning between the old and the new economic sociology. For a brief survey of this literature review using the principal investigators of current aforementioned.